Mutations of the PIK3CA gene in patients with breast cancer in the Krasnoyarsk region - A. V. Zyuzyukina; E. Yu. Yakunina; V. I. Borodulina; L. A. Vasilovskaya; E. V. Slepov; V. A. Komissarova; R. A. Zukov (ABV-press, 2024)
Aim. To identify population characteristics of the PIK3CA gene mutation among breast cancer patients in the Krasnoyarsk region.Materials and methods. The study included 140 patients with breast cancer with a certain mutation status of the PIK3CA gene, observed at the Krasnoyarsk Regional Clinical Oncology Center named after A.I. Kryzhanovsky. Determination of PIK3CA gene mutations (exons 2, 5, 8, 10 and 21) was carried out using commercial kits on equipment from Roche (Germany). Statistical processing of the obtained data was carried out using Microsoft Excel and Statistica 12 software products. The assessment of the factor of influence on the relapse-free and overall survival was carried out by constructing and comparing Kaplan-Meier curves. The result was considered statistically significant at a significance level of p <0.05.Results and conclusion. The overall frequency of occurrence of PIK3CA gene mutations is 38.6 %. The most common mutations are H1047X (55.4 %) in exon 21 and E545K (27.8 %) in exon 10. The median age of breast cancer patients with mutation status in the PIK3CA gene was 58.9 [49.0; 67.0] years, median time to relapse or progression was 62.2 [27.0; 84.0] months. There were no statistically significant differences in relapse-free survival between the presence and absence of mutations (p = 0.8). The effect of changes in PIK3CA on a decrease in overall survival rates (p = 0.047) in breast cancer patients was shown.